1989
DOI: 10.1007/bf00024664
|View full text |Cite
|
Sign up to set email alerts
|

On the role of calcium in indole-3-acetic acid movement and graviresponse in etiolated pea epicotyls

Abstract: To determine whether Ca2+ plays a special role in the early graviresponse of shoots, as has been reported for roots, we treated etiolated pea epicotyls with substances known to antagonize Ca2+ (La3+), to remove Ca2+ from the wall (spermidine, EGTA), to inhibit calmodulin mediated reactions (chlorpromazine), or to inhibit IAA transport (TIBA). We studied the effect of these substances on IAA and Ca2+ uptake into 7 mm long subapical 3rd internode etiolated pea epicotyl sections and pea leaf protoplasts, on pea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
3
0
2
Order By: Relevance
“…5) is consistent with the previously described insensitivity of net NAA uptake to changes in the effiux contribution that was discussed by Sabater and Rubery (1987b). Migliaccio and Galston (1989) found that both Ca z + and La 3 + stimulated auxin uptake into tap-water-grown pea epicotyl segments from weakly buffered media. They suggested a common external site of cation action, perhaps via calmodulin, which is present in pea plasma membrane (Collinge and Trewavas 1989) but apparently absent from pea cell walls (Dauwalder et al 1986).…”
Section: Amelioration Of Auxin Efjlux and Its Npa-sensitivity By Addimentioning
confidence: 99%
“…5) is consistent with the previously described insensitivity of net NAA uptake to changes in the effiux contribution that was discussed by Sabater and Rubery (1987b). Migliaccio and Galston (1989) found that both Ca z + and La 3 + stimulated auxin uptake into tap-water-grown pea epicotyl segments from weakly buffered media. They suggested a common external site of cation action, perhaps via calmodulin, which is present in pea plasma membrane (Collinge and Trewavas 1989) but apparently absent from pea cell walls (Dauwalder et al 1986).…”
Section: Amelioration Of Auxin Efjlux and Its Npa-sensitivity By Addimentioning
confidence: 99%
“…The latter is one of the main mechanisms by which instructive auxin gradients in tissues are formed to regulate plant development. Interestingly, polar auxin transport was found to be highly dependent on Ca 2+ availability [ 104 , 121 , 122 , 123 , 124 , 125 ]. Together, these findings highlight the importance of Ca 2+ in auxin transport.…”
Section: Ca 2+ Controls the Rate Of Auxin Transmentioning
confidence: 99%
“…Calcium is a necessary component for the gravitropic response of stems (Migliaccio & Galston 1989), coleoptiles (Goswami & Audus 1976) and roots (Lee, Mulkey & Evans 1983a), but its exact role is still obscure. Current models (e.g.…”
Section: Introductionmentioning
confidence: 99%